Complexity Leadership Theory: An Interactive Perspective on Leading in Complex Adaptive Systems - Lichtenstein, Uhl-Bien; Schreiber, Orton; Lichtenstein, Benyamin; Uhl-Bien, Mary; Marion, Russ; Seers, Anson; Orton, James Douglas; Schreiber, Craig (Emergence, 2006)
Traditional, hierarchical views of leadership are less and less useful given the complexities of our modern world. Leadership theory must tr ansition to new perspec-tives that account for the complex adaptive ne eds of organizations. In this paper, we propose that leadership (as op posed to leaders) can be seen as a complex dynamic process that emerge s in the interactive "spaces between" people and ideas. That is, leade rship is a dynamic that transcends the capabilities of individuals alo ne; it is the product of interaction, tension, and exchange rules gove rning changes in per-ceptions and understanding. We label this a dynam ic of adaptive leadership, and we show how this dynamic provides impor tant insights about the nature of leadership and its outcomes in organ izational fields. We define a leadership event as a perceived segment of action whose meaning is created by the interactions of actors invol ved in producing it, and we present a set of innovative methods for ca pturing and analyzing these contextually driven processes. We provide theoretical and practical implications of these ideas for organization al behavior and organization and management theory.